Comparative Genomic and Phylogenetic Analysis of a Shiga Toxin Producing Shigella sonnei (STSS) Strain - Sváb, Domonkos; Bálint, Balázs; Vásárhelyi, Bálint; Maróti, Gergely; Tóth, István (Frontiers in Cellular and Infection Microbiology, 2017)
Shigella strains are important agents of bacillary dysentery, and in recent years S. sonnei has emerged as the leading cause of shigellosis in industrialized and rapidly developing countries. More recently, several S. sonnei and S. flexneri strains producing Shiga toxin (Stx) have been reported from sporadic cases and from an outbreak in America. In the present study we aimed to shed light on the evolution of a recently identified Shiga toxin producing S. sonnei (STSS) isolated in Europe. Here we report the first completely assembled whole genome sequence of a multidrug resistant (MDR) Stx-producing S. sonnei (STSS) clinical strain and reveal its phylogenetic relations. STSS 75/02 proved to be resistant to ampicillin, streptomycin, tetracycline, chloramphenicol, thrimetoprim and sulfomethoxazol. The genome of STSS 75/02 contains a 4,891,717 nt chromosome and seven plasmids including the 214 kb invasion plasmid (pInv) harboring type III secretion system genes and associated effectors. The chromosome harbors 23 prophage regions including the Stx1 converting prophage. The genome carries all virulence determinants necessary for an enteroinvasive lifestyle, as well as the Stx1 encoding gene cluster within an earlier described inducible converting prophage. In silico SNP genotyping of the assembled genome as well as 438 complete or draft Shigella sonnei genomes downloaded from NCBI GenBank revealed that S. sonnei 75/02 belongs to the more recently diverged global MDR lineage (IIIc). Targeted screening of 1131 next-generation sequencing projects taken from NCBI Short Read Archive of confirms that only a few S. sonnei isolates are Stx positive. Our results suggest that the acquisition of Stx phages could have occurred in different environments as independent events and that multiple horizontal transfers are responsible for the appearance of Stx phages in S. sonnei strains.